Nuevos registros de Otodontidae Glickman 1964B (Chondrichthyes) para el sur de la Península de Nicoya, Puntarenas, Costa Rica - Laurito, César A. (Universidad de Costa Rica, 2021)
The Otodus genus and its species have been recorded in Southern Central America since the Eocene epoch, its remains are associated with calcareous or clastic sediments typical of sublitoral or inner neritic environments. One of these geological formations is Santa Teresa Fm. with a Middle Miocene to Lower Pliocene age range, outcropping in the Pacific margin and the elevated parts at the southern end of the Nicoya Peninsula, where a series of finds of Otodus (Megaselachus) chubutensis and Otodus (Megaselachus) megalodon had been previously reported. Over several decades, dental remains associated with Otodus genus have been recorded at Southern Nicoya Peninsula, fortuitous finds, some of them without direct geological context. However, the locations given by the people who made the findings, allow us to establish with some degree of certainty the sedimentary units from which the samples came, allowing us to increase the knowledge of the abundance and diversity of the fossil record of these giant sharks.